Simultaneous multiplicate age-season adjustment factors for milk yield in holstein cows - Martinez, Mário Luiz (Pesquisa Agropecuaria Brasileira, 1991)
Maximum likelihood was used to estimate ageseason adjustment factors for milk yield from 60,257 lactations of 27,842 cows that calved between 1975 and 1987 in 549 herds for three levels of herd production: low (3,660 kg), average (4,690 kg) and high (5,369 kg) Maximum milk yield was between 7 and 9 years of age, regardless of herd level. Adjustment factors at mature age for cows calving in the rainy (October to March) season were 3 to 5% greater than the factors obtained in the dry (April to September). Factors obtained in the average herd level can be used for cows calving at ages between 2 and 9 years in the dry season in all herd levels of production. For the rainy season, different sets of factors should be used, based on the herd level.